Risiko Perilaku Makan Selama Hamil Terhadap Kejadian Preeklamsia Di Puskesmas Panekan Tahun 2018: The Risk of Eating Behavior During Pregnancy on the Incidence of Preeclampsia at Panekan Health Center in 2018 - Anik Suparti; Suparji Suparji; Nana Usnawati (Gema Bidan Indonesia, 2021)
Preeclampsia (PE) is a contributor to mortality and morbidity of mothers and babies. Preeclampsia is the second biggest cause of maternal mortality, affecting 3% to 8% of pregnant women worldwide. The prevalence of preeclampsia in pregnant women in Magetan in 2017 as many as 189 people, while in 2018 as many as 270 people. An increase in the incidence of pre-eclampsia from 2017 to 2018 as many as 81 people. The research objective to analyze the risks of eating behavior during pregnancy on the incidence of preeclampsia in Puskesmas Panekan 2018. This study is a retrospective observational analytic approach (case- control). The subjects were birth mothers, 27 respondents in the case group and 27 respondents in the control group, for a total of 54 respondents. Data was collected by using a questionnaire, conducted on birth mothers in Puskesmas Panekan Year 2018. The analysis technique used is logistic regression. The results used logistic regression eating behavior p value = 0.00 (p <0.05) and OR (Exp B) 35.714. Based on the description above can be concluded that the eating behavior influenced the incidence of preeclampsia. pregnant women who have unhealthy eating behaviors have 35x greater risk for preeclampsia than women who have healthy eating behaviors, so it is advised untuk reduce the incidence of pre-eclampsia in pregnant women with preeclampsia risk factor control needed in pregnancy that is by implementing a healthy eating behavior. Keywords :Preeclampsia, eating behavior.